SISTEM PENDUKUNG KEPUTUSAN MUTASI PEGAWAI BERBASIS DESKTOP DENGAN METODE PROMETHEE PADA BKDSM KABUPATEN TTU - Maria Millenia Pina Lewuk; Yoseph P.K Kelen; Darsono Nababan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2023)
Quality human resources is a determining factor for the success of an organization in achieving its goals, including government agencies and their apparatus. One way to look for human resour es is quality, namely through the transfer of tasks. Transfer of tasks or mutations really need to be done as State Civil Apparatus (ASN) career planning and also to rejuvenate a position. Proposal process ASN the will be transferred to the TTU Regency BKDSM office use analysis or random selection of ASN manual by considering several criteria, which then the proposal is sent to the BKN office using the MYSAPK application. Because the analysis of ASN selection is still manual, the analysis of ASN selection is still manual, the researchers propose a This desktop-based decicion support system with the method used is the promethee method or ranking because the method is a multi-criteria method that can handle qualitative data and quantitatively at once, so that is can easily determine ASN candidates who are transferred according to the criteria selection of ASN namely competence, performance, qualifications and discipline. The results of this study are, the application of the SPK-Mutations that can simplify the process of selecting appropriate ASN are proposed for mutations.